An analysis of the Australian illicit tobacco market. Issue 1 (3rd January 2017) - Lauchs, Mark; Keane, Rebecca
Abstract : Purpose: This paper aims to provide an overview of the illicit tobacco market in Australia. It attempts to build a picture of the sources of demand, size of the market and methods of supply. Design/methodology/approach: This paper is based on collation of disparate government reports, industry research, media and court documents. It is a preliminary paper in the absence of better source data. Findings: The market is driven by the extremely high tax on tobacco in Australia. Australia's geography emphasises on large shipments from overseas rather than small-scale smuggling. The likely market is for migrant communities with much higher smoker rates than in the mainstream community. Research limitations/implications: It is not yet possible to conduct a well-focused research because of limited official documentation. Practical implications: Few government agencies focus on tobacco smuggling, and there are no publications providing a strategic picture of the illicit market. This paper fills this gap by collating multiple sources to produce a market profile. Social implications: The Australian Government loses 1bn per year in tobacco tax because of smuggling. The illicit supply also means that the social goal of the tax, namely, dissuading tobacco consumption, is undermined. Originality/value: There are no academic or government publications describing the Australian illicit tobacco market. The only publications are based on research funded by the tobacco industry, which has a vested interest in overstating the size of the illicit market.